Evaluation of the Tax-Free Parking Policy Improving Quality of Public Services in Jember Regency - Miftakhul Laily, Yaen; Erasandi, Senato; Maulana, Fajri; Nanda Al Hakim Akbar, Muhamad (Asosiasi Ahli Administrasi Indonesia, 2026)
This study aims to evaluate the free parking policy implemented in Jember Regency and its impact on the quality of public services and the local economy. This policy was launched to reduce the burden on the community in paying parking fees and to increase population mobility. Using a qualitative approach, this study analyses data through field observations and documentation studies. The results of the study show that this policy has succeeded in reducing the financial burden on the community and improving accessibility to public facilities. However, there are challenges related to the decline in regional revenue from the parking sector, which needs to be offset by other alternative sources of revenue, such as regional taxes. This study suggests the need for periodic evaluations to ensure the sustainability of this policy and its positive impact on the local economy and public infrastructure. A comprehensive evaluation will be crucial to assess the effectiveness of this policy in the long term.